2017
DOI: 10.1371/journal.pone.0187400
|View full text |Cite
|
Sign up to set email alerts
|

Employing open/hidden administration in psychotherapy research: A randomized-controlled trial of expressive writing

Abstract: Psychotherapy has been shown to be effective, but efforts to prove specific effects by placebo-controlled trials have been practically and conceptually hampered. We propose that adopting open/hidden designs from placebo research would offer a possible way to establish specificity in psychotherapy. Therefore, we tested the effects of providing opposing treatment rationales in an online expressive writing intervention on affect in healthy subjects. Results indicate that it was possible to conduct the expressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…For example, a number of meta-analyses showed that various bona fide psychotherapies, i.e., therapies with a clear treatment rationale but with very different underlying theories, aims, and methods appear to be equally effective (Spielmans et al., 2007; Cuijpers et al., 2008; Barth et al., 2013; Frost et al., 2014). In addition, opposing treatment approaches with the same treatment rationale have shown to be equally effective in a trial on clients with panic disorder (Kim et al., 2012) as much as similar treatments provided with opposing treatment rationales have shown to differ in their effects (Tondorf et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of meta-analyses showed that various bona fide psychotherapies, i.e., therapies with a clear treatment rationale but with very different underlying theories, aims, and methods appear to be equally effective (Spielmans et al., 2007; Cuijpers et al., 2008; Barth et al., 2013; Frost et al., 2014). In addition, opposing treatment approaches with the same treatment rationale have shown to be equally effective in a trial on clients with panic disorder (Kim et al., 2012) as much as similar treatments provided with opposing treatment rationales have shown to differ in their effects (Tondorf et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies investigating placebo effects have concentrated on patients' consciously-held beliefs that a treatment will be effective (Berna et al, 2017;Vase et al, 2005). Patients' expectations in augmenting placebo effects are perhaps most clearly observed in so-called "open-hidden" experimental investigations (Amanzio et al, 2001;Tondorf et al, 2017). For example, in an experiment in a hospital setting, intravenous analgesics were administered to patients covertly (from another room) or openly (in full view of the patient).…”
Section: Mechanisms and Pathways Of Placebo And Nocebo Effectsmentioning
confidence: 99%
“…However, it is also commonly theorized that expectancies can be shaped by other pathways, such as learning processes, particularly conditioning (Amanzio and Benedetti, 1999;Benedetti et al, 2003b); verbal instructions including the provision of a treatment rationale (Locher et al, 2017;Tondorf et al, 2017); and perceptions about others. Classical-or "Pavlovian"-conditioning refers to the learned associations between a neutral stimulus (e.g.…”
Section: Mechanisms and Pathways Of Placebo And Nocebo Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups received the same online expressive writing intervention but different treatment rationales: participants in the open-arm were told that the intervention had beneficial effects on mood in the long-run whereas participants in the hidden-arm were informed that mood only influenced how they perform in the intervention. Significant differences were observed as shown by a long-term decrease of negative affect in the open-arm only (Tondorf et al, 2017 ). However, this study included healthy subjects and the design should still be tested in a clinical setting.…”
Section: What Are the Solutions?mentioning
confidence: 99%